Glyceryl Laurate Tablets: Effect of the Excipients and Granule Size on the Tablet Quality - Špaglová M.; Papadakos M.; Čuchorová M.; Krchňák D.; Šimunková V.; Matušová D. (Sciendo, 2023)
Glyceryl laurate (GL) is a natural or synthetic surfactant with antiviral and antimicrobial activity and is not only effective in common colds or flu, but also against swine flu, herpes simplex, shingles, or chronic fatigue. The study aimed to formulate the GL granules as a semi-product for the compression of tablets and evaluate the influence of the substitution of sucrose laurate (Ryoto®) with sucrose ester (Sisterna®) in the composition of the granules and the effect of granule size on the quality of the compressed tablets. Four types of granules, varying in grain size and the type of additional surfactant, were prepared by melt granulation. The traditional pharmacopoeia tests were used to assess tablets' quality. The granule size significantly affected all evaluated parameters: hardness, uniformity of mass, friability, and disintegration. The replacement of sucrose laurate with sucrose ester caused a slight decrease in tablet strength and a shortening of disintegration. However, it did not significantly impact friability and uniformity of mass. For this reason, the excipient, sucrose ester, can be evaluated as an adequate replacement in the composition of GL tablets.